An Examination of Florida Hospices: Does For-Profit or Nonprofit Status Impact the Quality of Patient Care? (Global Journal of Management and Business Research, 2017)
When the Medicare Hospice Benefit program was initially introduced, the market was dominated by non-profit hospices. Today, however, this is no longer the case. Although nonprofits are often associated with a higher quality of care, the financial incentives created by the Medicare Hospice Benefit program have resulted with a for-profit dominated market. The specific problem examined was the impact of organizational constructs on the quality of patient care in the state of Florida. The purpose of this study was to determine whether any significant differences were present in the quality of hospice patient care resulting from differing ownership types utilizing a Contingency Theory approach. A quantitative comparative analysis was conducted utilizing descriptive statistics and ANOVA analyses. The participants for the study included all licensed Florida hospices that submitted the State of Florida Department of Elder Affairs Hospice Demographic and Outcome Measures Report between 2010 and 2015. The findings indicated an underrepresentation of for-profit hospices in the state of Florida, with no statistically significant differences between the quality of care in for-profit and nonprofit hospices. Both of these findings are inconsistent with previous research.